Attenuation of oxidative hemolysis of human red blood cells by the natural phenolic compound, allylpyrocatechol. (September 2013) - Iyer, M. K.; Nayak, R.; Colah, R.; Chattopadhyay, S.
Abstract The protecting ability of the Piper betle leaves-derived phenol, allylpyrocatechol (APC) against AAPH-induced membrane damage of human red blood cells (RBCs) was investigated. Compared to control, AAPH (50 mM) treatment resulted in significant hemolysis (55%, p < 0.01), associated with increased malondialdehyde (MDA) (2.9-fold, p < 0.001) and methemoglobin (6.1-fold, p < 0.001) levels. The structural deformation due to membrane damage was confirmed from scanning electron microscopy (SEM) images and Heinz bodies formation, while the cell permeability was evident from the K+ efflux (28.7%, p < 0.05) and increased intracellular Na+ concentration (8%, p < 0.05). The membrane damage, due to the reduction of the cholesterol/phospholipids ratio and depletion (p < 0.001) of ATP, 2, 3-DPG by ˜44–54% and Na+–K+ ATPase activity (43.7%), indicated loss of RBC functionality. The adverse effects of AAPH on all these biochemical parameters and the resultant oxidative hemolysis of RBCs were significantly reduced by pretreating the cells with APC (7 μM) or α-tocopherol (50 μM) for 1 h, prior to incubation with AAPH.